The relationship between dating violence and help-seeking behavior among adolescents aged 12-14 - Ayu, Suci Musvita; Septiyaningrum, Berlianna; Wenerda, Indah; Jatmika, Septian Emma Dwi (Jurnal Cakrawala Promkes, 2024)
Dating violence is a manifestation of inequality in any given relationship. It involves abuse within a romantic relationship that inflicts both physical and psychological harms on the victim. The psychological impacts include heartbreak, loss of self-confidence, and anxiety. This issue is particularly concerning among adolescents and warrants attention from various stakeholders. Consequently, seeking help is crucial for individuals who experience dating violence. This paper aims to assess the relationship between incidents of dating violence and the help-seeking efforts of victims. This study was a cross-sectional survey that was conducted at Junior High School.  82 respondents were recruited by utilizing relationship between dating violence and help seeking behavior was analyzed using Chi-Square. The majority of respondents who experienced dating violence reported emotional violence (25.6%) and 48.8% of these individuals did not seek help. The results indicate no significant relationship between incidents of dating violence and help seeking behavior among Adolescents aged 12–14 years old in Yogyakarta X2 (1, N = 104) = 1.7, p > .05. This suggested that, within this study, there is no significant correlation between the occurrence of dating violence and efforts made by adolescents to seek help. Despite experiencing violence, these adolescents may not be inclined to reach out for assistance, suggesting a potential disconnect between the experiencing violence and responding to it.